Exploring The Impact of Work-Family Conflict and Self-Efficacy on Work-Life Balance Among Factory-Working Mothers: A Quantitative Analysis - Auliyah, Nuris Syifa; Kawuryan, Fajar (Golden Ratio of Social Science and Education, 2025)
Work-life balance is a significant challenge for working mothers, especially those in the industrial sector, as they must simultaneously manage job demands and family responsibilities. This study aims to empirically examine the relationship between work-family conflict and self-efficacy with work-life balance among mothers working in factories. A quantitative method with purposive sampling techniques was used. The respondents were mothers employed in the production section of factories, and the instruments used included scales of work-life balance, work-family conflict, and self-efficacy. The analysis revealed a highly significant relationship between work-family conflict and self-efficacy with work-life balance, with a correlation coefficient of 0.694 and a significance value of p = 0.000 (p < 0.01). The first minor hypothesis showed a highly significant negative relationship between work-family conflict and work-life balance (r = -0.679; p < 0.01), while the second minor hypothesis showed a highly significant positive relationship between self-efficacy and work-life balance (r = 0.525; p < 0.01). These findings indicate that lower levels of work-family conflict and higher levels of self-efficacy can enhance mothers' ability to achieve a balanced work and personal life. The results have important implications for developing support strategies for working women, particularly in managing dual roles and enhancing self-efficacy to achieve a better work-life balance.